Traditional Chinese medicine manual therapy for adolescent idiopathic scoliosis: a case report - Zhu, Bowen; Li, Miaoxiu; Ren, Jun; He, Tianxiang; Zhou, Xin; Wang, Shoujian; Kong, Lingjun; Fang, Min (Frontiers in Pediatrics, 2025)
ObjectivesThis case demonstrates the efficacy and safety of Traditional Chinese Medicine manual therapy (TCMMT) for the treatment of mild to moderate AIS.MethodsAn 10-year-old girl who suffered from low back pain (LBP) with marked shoulder inequality and razorback postural abnormalities, with a clinical diagnosis of idiopathic scoliosis, and the Cobb angle of 20° and angle of trunk rotation (ATR) of the thoracic vertebral segment at 7°, and ATR of the lumbar vertebral segment at 8°, was treated with TCMMT. The patient initially recovered from centralized LBP with repeated TCMMT twice per week for 1 month. Subsequently, the frequency of TCMMT treatment was changed to 1–2 sessions weekly for 6 months. Before treatment, after the first TCMMT, 1 month and 7 months of treatment, and 18 months of follow-up, we used ATR or Cobb angle and health-related quality of life (HRQOL) for assessment. The HRQOL was assessed using the visual analog scale (VAS) scores and the Scoliosis Research Society-22 (SRS-22) patient questionnaire. The minimum clinically important difference (MCID) was used to assess the effectiveness of clinical measures based on a “responder analysis”.Results(a) The patient's VAS score was 40/100 before treatment, 25/100 after the first treatment, 15/100 after 1 month of treatment, 12/100 after 7 months of treatment, and 15/100 at follow-up to 18 months. (b) The patient's SRS-22 score was 54/110 before treatment, 61/110 after the first treatment, 79/110 after 1 month of treatment, 106/110 after 7 months of treatment, and 104/110 at follow-up to 18 months. (c) Before treatment, the patient's thoracic ATR angle was 7° and the lumbar ATR angle was 8°, there was no change in the ATR angles of the thoracic and lumbar spine after the first treatment. The thoracic ATR angle was 6° and the lumbar ATR angle was 5° after 1 month of treatment. The thoracic ATR angle was 1.5° and the lumbar ATR angle was 3.5° after 7 months of treatment. The thoracic ATR angle was 2° and the lumbar ATR angle was 4° at the follow up till 18 months. (d) The patient's Cobb angle was 20° before treatment, 7° after the 7 month of treatment, and 8° at follow-up to 18 months. No adverse events during treatment.ConclusionsTCMMT is a conservative treatment option worthy of consideration when considering a conservative treatment strategy for AIS.